Accessing the Anisotropic Nonthermal Phonon Populations in Black Phosphorus - Seiler, Hélène; Zahn, Daniela; Zacharias, Marios; Hildebrandt, Patrick-Nigel; Vasileiadis, Thomas; Windsor, Yoav William; Qi, Yingpeng; Carbogno, Christian; Draxl, Claudia; Ernstorfer, Ralph; Caruso, Fabio (My University, 2021)
We combine ultrafast electron diffuse scattering experiments and first-principles calculations of the coupled electron-phonon dynamics to provide a detailed momentum-resolved picture of lattice thermalization in black phosphorus. The measurements reveal the emergence of highly anisotropic nonthermal phonon populations persisting for several picoseconds after exciting the electrons with a light pulse. Ultrafast dynamics simulations based on the time-dependent Boltzmann formalism are supplemented by calculations of the structure factor, defining an approach to reproduce the experimental signatures of nonequilibrium structural dynamics. The combination of experiments and theory enables us to identify highly anisotropic electron-phonon scattering processes as the primary driving force of the nonequilibrium lattice dynamics in black phosphorus. Our approach paves the way toward unravelling and controlling microscopic energy flows in two-dimensional materials and van der Waals heterostructures, and may be extended to other nonequilibrium phenomena involving coupled electron-phonon dynamics such as superconductivity, phase transitions, or polaron physics.
Keywords: Black phosphorus; Electron−phonon coupling; First-principles calculations; Layered materials; Ultrafast electron diffraction